Colacium vesiculosum : A new record for Bangladesh - Khondker, Moniruzzaman; Bhuiyan, Rauf Ahmed; Yeasmin, Jenat (Bangladesh Journal of Botany, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> A colonial euglenoid alga Colacium vesiculosum Ehrenberg is reported for the first time in Bangladesh. The species has been taxonomically described with photomicrographs. It was collected from Mathbaria of Pirojpur district. Key words: Colacium vesiculosum, Euglenoid alga, New record, Bangladesh. DOI = 10.3329/bjb.v36i2.1514 Bangladesh J. Bot. 36(2): 195-197, 2007 (December)